Investors Sentiment and Stock Return; Evidence from Pakistan Stock Exchange (PSX) - Sikandar Rahman; Syyed Ali Raza Kazmi; Muhammad Ramzan (International Journal of Business and Economic Affairs, 2022)
The attitude of investors prevailing as to expected price development in a market is known as investors’ sentiment. A strong correlation exists between individual investor sentiment and their attitudes, so investor behavior can influence the stock market and cause the reason for to fluctuate the stock prices. The purpose of the study was to examine market actions of investor sentiment and provide market-based evidence regarding the growth of the stock market and the individual investor beliefs. Variables used as proxies were Consumer Confidence Index (CCI) and trading volume. This study was conducted on Pakistan Stock Market for 2 years. Monthly return and trading volume data of KSE-100 stocks were used in the study for the period from November 2017 to November 2019. De-listed, suspended and default counter stocks were excluded. An ordinary linear regression was run to find investor sentiment effects on returns and trading volume. The results proved positive relation between changes in CCI, trading volume, and stock returns.